Listening in the Moment: How Bilingualism Interacts With Task Demands to Shape Active Listening - Krizman, Jennifer; Tierney, Adam; Nicol, Trent; Kraus, Nina (Frontiers in Neuroscience, 2021)
While there is evidence for bilingual enhancements of inhibitory control and auditory processing, two processes that are fundamental to daily communication, it is not known how bilinguals utilize these cognitive and sensory enhancements during real-world listening. To test our hypothesis that bilinguals engage their enhanced cognitive and sensory processing in real-world listening situations, bilinguals and monolinguals performed a selective attention task involving competing talkers, a common demand of everyday listening, and then later passively listened to the same competing sentences. During the active and passive listening periods, evoked responses to the competing talkers were collected to understand how online auditory processing facilitates active listening and if this processing differs between bilinguals and monolinguals. Additionally, participants were tested on a separate measure of inhibitory control to see if inhibitory control abilities related with performance on the selective attention task. We found that although monolinguals and bilinguals performed similarly on the selective attention task, the groups differed in the neural and cognitive processes engaged to perform this task, compared to when they were passively listening to the talkers. Specifically, during active listening monolinguals had enhanced cortical phase consistency while bilinguals demonstrated enhanced subcortical phase consistency in the response to the pitch contours of the sentences, particularly during passive listening. Moreover, bilinguals’ performance on the inhibitory control test related with performance on the selective attention test, a relationship that was not seen for monolinguals. These results are consistent with the hypothesis that bilinguals utilize inhibitory control and enhanced subcortical auditory processing in everyday listening situations to engage with sound in ways that are different than monolinguals.